2018
DOI: 10.1589/jpts.30.23
|View full text |Cite
|
Sign up to set email alerts
|

The effect of actively induced vibration using shoulder joint on pain and dysfunction in patients with low back pain

Abstract: [Purpose] This study aimed to determine the effect of a Flexi-Bar exercise program with vibration stimulation on pain and dysfunction in patients with low back pain. [Subjects and Methods] This study included 30 patients with low back pain. The participants were divided into a control (n=15) group and an experimental group (n=15). General physical therapy was used in both groups. A Flexi-Bar exercise program with vibration stimulation was used in the experimental group. The Visual Analog Scale was used to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
1
5
0
1
Order By: Relevance
“…Vibrational stimulation provokes the mechanical receptors such as Pacini and Meissner, which sense the vibrations, then A-beta myelinated fibers transmitted this sense of vibrations to the posterior horn of the spinal cord and suppresses pain transmission to the higher centers (29). Also, vibrational stimulation reduces the level of P substance in the CSF and has a neurophysiological placebo effect that reduces pain transmission from peripheral receptors to the brain (30). Additionally, vibratory stimulation triggers a tonic vibrational reflex (TVR).…”
Section: Discussionmentioning
confidence: 99%
“…Vibrational stimulation provokes the mechanical receptors such as Pacini and Meissner, which sense the vibrations, then A-beta myelinated fibers transmitted this sense of vibrations to the posterior horn of the spinal cord and suppresses pain transmission to the higher centers (29). Also, vibrational stimulation reduces the level of P substance in the CSF and has a neurophysiological placebo effect that reduces pain transmission from peripheral receptors to the brain (30). Additionally, vibratory stimulation triggers a tonic vibrational reflex (TVR).…”
Section: Discussionmentioning
confidence: 99%
“…17 Some studies have reported that long-term flexi-bar training has positive effects on the muscle mass, 18 19 muscle strength 20 and physical performance. 21 22 A study reported that the thickness of the transversus abdominis muscle of young university adults increases to 2.4 mm after a 6-month (48 times) flexi-bar training programme. 18 In another study, the overweight adults with a 12-week flexi-bar training programme exhibited a significant increase in handgrip strength, which was significantly different from that of the control group.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the device can maintain stability of force constantly 18) . Vibration generated by flexi bar will stimulate core muscle functioning [19][20][21] to generate reaction with the change of cross-sectional area of muscles and increase muscle activate throughout the body [22][23][24] . For core muscles in human body, training with flexi bar can help encourage the functioning system of nerve muscles to perform reaction faster 25,26) .…”
Section: Introductionmentioning
confidence: 99%